Sodium-ion battery diaphragm coating slurry, coated diaphragm and sodium-ion battery

By using carboxy sodium salt sodium supplement agent and inorganic solid electrolyte materials in the sodium ion battery separator coating layer, the problems of battery activity Na+ loss and poor thermal stability of the separator are solved, and battery capacity improvement and performance optimization are achieved.

CN119481578AInactive Publication Date: 2025-02-18HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD +1

Patent Information

Application Number
CN202510065353.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the first charging process, the active Na+ loss caused by the formation of SEI film and side reactions, reducing the reversible capacity; at the same time, the thermal stability and wettability of the polyolefin microporous separator are poor, resulting in poor battery safety and electrochemical performance. .

Method used

Using sodium ion battery separator coating slurry including carboxyl sodium salt sodium supplement agent, Na+ is used to distribute Na+ in the separator coating layer, compensate for the loss of active Na+ in the battery, and improve the thermal stability of the separator through inorganic solid electrolyte materials. and wettability.

Benefits of technology

It effectively compensates for the loss of active Na+ in the battery and improves the reversible capacity of the battery; at the same time, it improves the breathability, wetting and thermal stability of the membrane, and enhances the safety and electrochemical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481578A_ABST
    Figure CN119481578A_ABST
Patent Text Reader

Abstract

The invention provides sodium ion battery diaphragm coating slurry, a coated diaphragm and a sodium ion battery, and belongs to the technical field of energy materials. The raw materials comprise the following components: 5-60 parts of a sodium supplementing material, 50-90 parts of an inorganic solid electrolyte material, 0.1-3 parts of a dispersant, 1-10 parts of a binder, 0.1-5 parts of a wetting agent, 0-2 parts of an auxiliary agent and 100-300 parts of a solvent. The sodium-ion battery sodium-supplementing diaphragm comprises the sodium-ion battery sodium-supplementing diaphragm coating slurry and a base membrane, and at least one side of the base membrane is coated with the sodium-ion battery sodium-supplementing diaphragm coating slurry. According to the sodium-ion battery sodium-supplementing diaphragm prepared from the sodium-ion battery sodium-supplementing diaphragm coating slurry provided by the invention, the sodium-supplementing material in the diaphragm coating compensates sodium ions consumed by SEI film formation and side reaction by providing active Na < + >, so that the reversible capacity of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of energy materials, and in particular relates to a sodium ion battery diaphragm coating slurry, a coated diaphragm and a sodium ion battery. Background Art

[0002] During the first charge of a sodium-ion battery, the formation of a solid electrolyte interphase (SEI) membrane on the negative electrode side and some unknown side reactions will consume part of the active Na from the positive electrode material. + , resulting in the insertion of active Na into the cathode material during the first discharge. + Therefore, these irreversible electrochemical reactions will reduce the reversible capacity of sodium-ion batteries. An effective strategy to improve this problem is to use sodium supplementation technology. Sodium supplementation technology can effectively compensate for the active Na caused by the formation of SEI film. + loss and improve the cycle capacity of the battery.

[0003] At present, sodium supplementation technologies mainly include positive electrode sodium supplementation and negative electrode sodium supplementation. The positive and negative electrode sodium supplementation technologies are to add an appropriate amount of sodium supplementation agent when preparing the slurry. The sodium supplementation agent will undergo an irreversible oxidation reaction during the first charge, releasing a large amount of Na + , to compensate for the Na + loss, thereby increasing the reversible capacity of the entire battery. This method has a wide range of applications and is easy to operate. It avoids the cumbersome and complicated additional process of negative electrode sodium supplementation and is compatible with existing battery production processes, so it has received widespread attention. However, many sodium supplement materials have problems with gas production and inactive solid residues, which will reduce the capacity and cycle performance of the battery. The positive and negative electrode coatings are channels for sodium ions to enter the positive and negative electrode materials from the electrolyte. If the sodium supplement material is unevenly distributed in the coating or forms larger particles, it may block the channel for ion transmission, resulting in an increase in the internal resistance of the battery and a decrease in the charge and discharge performance.

[0004] Most of the carboxyl sodium salt sodium supplements reported so far have the characteristics of low cost, large theoretical specific capacity, suitable voltage range, and no residue. + A large amount of gas is generated. These gases can be discharged from the battery during the formation stage and will not have an adverse effect on the subsequent cycle of the battery. However, the holes left after the decomposition of the sodium supplement will destroy the structure of the electrode, thereby reducing the electrochemical performance.

[0005] Sodium-ion batteries generally use polyolefin microporous diaphragms, which have poor wettability to electrolytes and low thermal stability. When the temperature rises, the diaphragms will shrink, which will directly cause the battery to short-circuit, posing a safety hazard. To address this problem, the existing treatment method is to coat a ceramic layer (such as alumina, boehmite, silica, titanium dioxide, and magnesium oxide) on the surface of the base membrane. However, since these coating materials are not electrochemically active and the coating layer reduces the porosity and permeability of the diaphragm, the interface resistance of the sodium-ion battery increases, and the internal resistance increases, which is not conducive to improving the safety and electrochemical performance of the sodium-ion battery. Summary of the invention

[0006] This application aims to solve the problem of battery due to active Na + The problems of low reversible capacity caused by loss, low battery safety and poor electrochemical performance caused by poor thermal stability and wettability of the diaphragm are solved by providing a method to supplement the active Na + The invention relates to a sodium ion battery diaphragm coating slurry, a coated diaphragm and a sodium ion battery with high air permeability, good wettability, high thermal stability and high electrical conductivity.

[0007] In a first aspect, the present application provides a sodium ion battery diaphragm coating slurry, in which the raw materials include the following components, measured by mass: 5 to 60 parts of sodium supplement material, 50 to 90 parts of inorganic solid electrolyte material, 0.1 to 3 parts of dispersant, 1 to 10 parts of binder, 0.1 to 5 parts of wetting agent, 0 to 2 parts of auxiliary agent and 100 to 300 parts of solvent.

[0008] The sodium supplement material is a carboxyl sodium salt sodium supplement, including a combination of one or more of tetrasodium ethylenediaminetetraacetate, pentasodium diethylenetriaminepentaacetate, trisodium nitrilotriacetate, trisodium dicarboxymethylalanine, disodium iminodiacetate, trisodium citrate, sodium oxalate, and sodium squarate.

[0009] Carboxyl sodium salt sodium supplement material has the characteristics of low cost, stable chemical properties, and environmental friendliness. As a sodium supplement material for sodium ion batteries, it completely decomposes and releases Na during the first charging process of sodium ion batteries. + , carbon oxides and nitrogen oxides. + It can be used to compensate for the active Na consumed by the formation of negative electrode SEI film and side reactions in the battery. + The released gas can be discharged from the battery during the formation stage, and will not have an adverse effect on the subsequent cycle of the battery. Compared with the prior art in which sodium-supplementing materials are used to prepare the positive electrode, the present application uses sodium-supplementing materials for the diaphragm coating layer. The decomposition of the sodium-supplementing materials leaves pores in the diaphragm coating layer, which is beneficial to improving the permeability of the coated diaphragm and the wettability to the electrolyte.

[0010] The inorganic solid electrolyte material is a NASICON solid electrolyte or / and Beta-Na-Al2O3, and the particle size of the solid electrolyte powder is 0.1 to 50.0 μm. The inorganic solid electrolyte has high ion conductivity and can effectively conduct Na + , ensuring the normal operation of the battery, improving the battery's charge and discharge efficiency, reducing the loss of electrode materials, and extending the battery's service life. In addition, the interface compatibility between the inorganic solid electrolyte and the electrode material is good, which can reduce the interface impedance and improve the battery's charge and discharge efficiency and cycle stability.

[0011] The dispersant is a combination of one or more of sodium polyacrylate, polyethylene glycol, polyvinyl pyrrolidone, polymethacrylate, polyacrylate ammonium copolymer and polyvinyl alcohol; the binder is a combination of one or more of polyacrylate, polyacrylamide, polyvinyl alcohol, styrene-butadiene rubber, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polytetrafluoroethylene, carboxymethyl cellulose, sodium carboxymethyl cellulose, polymethyl methacrylate, polyacrylate and polyacrylonitrile; the wetting agent is polydimethylsiloxane, polyether-modified siloxane, poly The invention relates to a combination of one or more of ethylene oxide, polyoxyethylene alkylamine, octylphenol polyoxyethylene ether, polyether siloxane, sodium dodecylbenzene sulfonate and sodium lauryl sulfate; the auxiliary agent is a combination of one or more of sodium carboxymethyl cellulose, sodium alginate, polyglycol ether, polyoxyethylene amide, polyacrylamide, titanate coupling agent and sodium perfluorooctanoate; the solvent is a combination of one or more of deionized water, N-methylpyrrolidone, N,N-dimethylformamide, N,N-diethylformamide, dimethyl sulfoxide, tetrahydrofuran, ethanol and isopropanol.

[0012] The present invention is directed to the active Na + In order to solve the problems of decreased reversible specific capacity due to loss, low thermal stability and poor wettability of the diaphragm, a sodium-supplemented diaphragm coating slurry including a carboxyl sodium supplement is provided. The diaphragm coating slurry is coated on the surface of the diaphragm. During the first charging process of the battery, carboxyl sodium salt (R(COONa)) releases sodium ions and carbon and nitrogen oxide gases to supplement sodium to the battery. At the same time, the pores left in the diaphragm coating layer after the decomposition of the sodium supplement can improve the air permeability of the diaphragm, and are beneficial to the penetration of the electrolyte, thereby further increasing the wettability of the diaphragm. In addition, a solid electrolyte is used in the diaphragm coating slurry instead of inorganic particles to improve the thermal stability and wettability of the diaphragm while providing a sodium ion transmission channel, thereby improving the electrical conductivity of the diaphragm, reducing the internal resistance, and improving the electrochemical performance of the battery.

[0013] In a second aspect, the present application provides a sodium ion battery coated diaphragm, comprising a base film; at least one side of the base film is coated with a sodium ion battery diaphragm coating slurry as described in any one of the first aspects.

[0014] The sodium-ion battery sodium-supplementing diaphragm provided by the present invention comprises a sodium-supplementing material in the diaphragm coating layer which provides active Na + , compensate for the sodium ions consumed by SEI film formation and side reactions, and realize the improvement of battery reversible capacity; the pores left in the diaphragm coating by the decomposition of the sodium supplement material are conducive to improving the wettability and air permeability of the diaphragm, and effectively solve the problem of the diaphragm coating reducing the porosity and air permeability of the diaphragm; the inorganic solid electrolyte material can not only replace the ceramic powder to improve the wettability and thermal stability of the diaphragm, but also provide a sodium ion transmission channel to improve the ion conductivity, while reducing the required amount of liquid electrolyte, greatly improving the safety and electrochemical performance of the battery. The sodium ion battery sodium supplement diaphragm coating slurry provided by the present invention does not increase the process, does not require additional cost investment, and has no safety hazards. Through the synergistic effect of the sodium supplement material and the inorganic solid electrolyte material, a layer of sodium is coated on the surface of the diaphragm. + Compensation function, Na + The porous structure coating layer with good transmission channels and air permeability can more effectively improve the safety and electrochemical performance of the battery.

[0015] In a third aspect, the present application provides a sodium ion battery, comprising the sodium ion battery coated diaphragm as described in the second aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0017] Figure 1 SEM image of the coated diaphragm obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0018] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0019] A sodium ion battery diaphragm coating slurry comprises the following raw materials, measured by weight: 5 to 60 parts of sodium supplementing material, 50 to 90 parts of inorganic solid electrolyte material, 0.1 to 3 parts of dispersant, 1 to 10 parts of binder, 0.1 to 5 parts of wetting agent, 0 to 2 parts of auxiliary agent and 100 to 300 parts of solvent.

[0020] In some embodiments, the sodium supplement material is a carboxylate sodium salt sodium supplement agent, including one or a combination of more than one of sodium ethylenediaminetetraacetate, pentasodium diethylenetriaminepentaacetate, trisodium nitrilotriacetate, trisodium dicarboxymethylalanine, disodium iminodiacetate, trisodium citrate, sodium oxalate, and sodium squarate.

[0021] In some embodiments, the inorganic solid electrolyte material is a NASICON-type solid electrolyte or / and Beta-Na-Al2O3, and the particle size of the solid electrolyte powder is 0.1 - 50.0 μm.

[0022] In some embodiments, the NASICON-type solid electrolyte is Na 3+x Zr 2-y M y Si 3-z P z O 12 (0 ≤ x ≤ 1, 0 < y ≤ 2, 0 < z ≤ 2), and the M element is one or a combination of more than one of Mg, Zn, Y, Al, Ga, In, Ge, Sn, As, Sb, Fe, Sc, Cd, Co, Ni, Cr, Mn, Ti, V, Mo, Nb, Hf, La, Lu, Ta.

[0023] In some embodiments, the general formula of the Beta-Na-Al2O3 is M'2O·xAl2O3 (1 ≤ x ≤ 11), where the M' element is Na, or a mixed element of Na and one or several of Li, Mg, K, Rb, Ag, Y, Ti, Nb.

[0024] In some embodiments, the dispersant is one or a combination of more than one of sodium polyacrylate, polyethylene glycol, polyvinylpyrrolidone, polymethacrylate, ammonium polyacrylate copolymer, and polyvinyl alcohol; The binder is one or a combination of more than one of polyacrylate, polyacrylamide, polyvinyl alcohol, styrene-butadiene rubber, polyvinylidene fluoride, polyvinylidene fluoride - hexafluoropropylene copolymer, polytetrafluoroethylene, carboxymethyl cellulose, sodium carboxymethyl cellulose, polymethyl methacrylate, polyacrylate, and polyacrylonitrile; The wetting agent is one or a combination of more than one of polydimethylsiloxane, polyether-modified siloxane, polyoxyethylene ether, polyoxyethylene alkylamine, octylphenol polyoxyethylene ether, polyether siloxane, sodium dodecylbenzenesulfonate, and sodium lauryl sulfate; The auxiliary agent is one or a combination of more than one of sodium carboxymethyl cellulose, sodium alginate, polyglycol ether, polyoxyethylene amide, polyacrylamide, titanate coupling agent, and sodium perfluorooctanoate; The solvent is a combination of one or more of deionized water, N-methylpyrrolidone, N,N-dimethylformamide, N,N-diethylformamide, dimethyl sulfoxide, tetrahydrofuran, ethanol and isopropanol.

[0025] In a second aspect, the present application provides a sodium ion battery coated diaphragm, comprising a base film; at least one side of the base film is coated with the sodium ion battery diaphragm coating slurry described in any one of the first aspects.

[0026] In some embodiments, the base film is one or a combination of polyolefin porous film, PP / PE composite film, aramid, polyimide and non-woven fabric, and has a thickness of 5 to 50 μm.

[0027] In some embodiments, the sodium ion battery separator coating slurry is coated with a thickness of 0.5 to 10 μm; the coating method includes a combination of one or more of gravure roller coating, scraper coating, spin coating, spray coating, and roller coating.

[0028] In a third aspect, the present application provides a sodium ion battery, comprising a sodium ion battery coated diaphragm as described in any one of the second aspects.

[0029] The technical solution of the present application is illustrated below through specific embodiments and comparative examples.

[0030] In order to enable the above implementation details and operations of the present application to be clearly understood by those skilled in the art, and to significantly demonstrate the improved performance of the embodiments of the present application, the above technical solutions are illustrated by means of multiple embodiments below.

[0031] Embodiment 1: Preparation of a sodium ion battery separator coating slurry: 150 g of tetrasodium ethylenediaminetetraacetate, 800 g of inorganic solid electrolyte Na3Zr 1.8 Mg 0.2 Si2PO 12 , 10 g sodium polyacrylate and 1800 g deionized water were stirred and mixed evenly, and after sand grinding, 20 g polyacrylate, 10 g polydimethylsiloxane and 10 g sodium carboxymethyl cellulose were added and stirred and mixed evenly to obtain a sodium-supplemented diaphragm slurry. The diaphragm coating slurry was coated on one side of a 16 μm PE base film by coating, with a coating thickness of 4 μm, and dried at 60°C to obtain a sodium-supplemented coated diaphragm for a sodium ion battery.

[0032] Figure 1 This is a SEM image of the coated diaphragm obtained in Example 1. It can be seen from the figure that the diaphragm slurry is evenly coated on the surface of the PE diaphragm.

[0033] Embodiment 2: Preparation of a sodium ion battery separator coating slurry: The difference between this embodiment and embodiment 1 is that the components and contents are different.

[0034] Specifically, 100 g of diethylenetriamine pentaacetic acid pentasodium, 820 g of inorganic solid electrolyte Na3Zr 1.8 Mg 0.2 Si2PO 12 , 10 g sodium polyacrylate and 2000 g deionized water were mixed evenly, and after sand grinding, 40 g polyacrylate, 20 g polydimethylsiloxane and 10 g sodium carboxymethyl cellulose were added and stirred to obtain a sodium-supplemented diaphragm slurry. The diaphragm coating slurry was coated on one side of a 16 μm PE base film by coating, with a coating thickness of 4 μm, and dried at 60°C to obtain a sodium-supplemented coated diaphragm for sodium ion batteries.

[0035] Embodiment 3: Preparation of a sodium ion battery separator coating slurry: The difference between this embodiment and embodiment 1 is that the components and contents are different.

[0036] Specifically, 150 g of trisodium nitrilotriacetate, 800 g of inorganic solid electrolyte Na3Zr 1.8 Mg 0.2 Si2PO 12 , 10 g sodium polyacrylate and 1800 g deionized water were mixed evenly, and after sand grinding, 20 g polyacrylate, 10 g polydimethylsiloxane and 10 g polyacrylamide were added and stirred to obtain a sodium-supplementing diaphragm slurry. The diaphragm coating slurry was coated on both sides of the 16 μm PE base film by coating, and the coating thickness on both sides was 4 μm. After drying at 60°C, a sodium-supplementing coated diaphragm for sodium ion batteries was obtained.

[0037] Embodiment 4: Preparation of a sodium ion battery separator coating slurry: The difference between this embodiment and embodiment 1 is that the components and contents are different.

[0038] Specifically, 150 g of tetrasodium ethylenediaminetetraacetate, 800 g of inorganic solid electrolyte Beta-Na-Al2O3, 10 g of sodium polyacrylate and 1800 g of N-methylpyrrolidone were mixed evenly, and after sand grinding, 20 g of polyvinylidene fluoride, 10 g of polydimethylsiloxane and 10 g of polyglycol ether were added and stirred to obtain sodium-supplementing diaphragm slurry. The diaphragm coating slurry was coated on one side of the 16 μm PE base film by coating, with a coating thickness of 4 μm, and dried at 80°C to obtain a sodium-supplementing coated diaphragm for sodium-ion batteries.

[0039] Comparative Example 1: The difference between this comparative example and Example 1 is that no sodium supplement material is contained in the diaphragm slurry, and the rest is the same as Example 1.

[0040] Preparation of a diaphragm coating slurry: 800 g of inorganic solid electrolyte Na3Zr 1.8 Mg 0.2 Si2PO 12 , 10 g sodium polyacrylate and 1800 g deionized water were stirred and mixed evenly, and after sand grinding, 20 g polyacrylate, 10 g polydimethylsiloxane and 10 g sodium carboxymethyl cellulose were added and stirred and mixed evenly to obtain a diaphragm slurry. The diaphragm coating slurry was coated on one side of the PE base film by coating, and dried at 60°C to obtain a sodium ion battery coated diaphragm.

[0041] Comparative Example 2: The difference between this comparative example and Example 1 is that, except that alumina ceramic powder is used in the diaphragm slurry instead of the inorganic solid electrolyte, everything else is the same as Example 1.

[0042] Preparation of a sodium ion battery separator coating slurry: 150 g of tetrasodium ethylenediaminetetraacetate, 800 g of alumina ceramic powder, 10 g of sodium polyacrylate and 1800 g of deionized water are stirred and mixed evenly, and after sand grinding, 20 g of polyacrylate, 10 g of polydimethylsiloxane and 10 g of sodium carboxymethyl cellulose are added and stirred and mixed evenly to obtain a sodium supplement separator slurry. The separator coating slurry is coated on one side of a PE base film by coating, and dried at 60°C to obtain a sodium ion battery sodium supplement coating separator.

[0043] Comparative Example 3: The difference between this comparative example and Example 1 is that alumina ceramic powder is used in the diaphragm slurry instead of the solid electrolyte material and no sodium supplement material is included, and the rest is the same as Example 1.

[0044] Preparation of a diaphragm coating slurry: 800 g of alumina ceramic powder, 10 g of sodium polyacrylate and 1800 g of deionized water are stirred and mixed evenly, and after sand grinding, 20 g of polyacrylate, 10 g of polydimethylsiloxane and 10 g of sodium carboxymethyl cellulose are added and stirred and mixed evenly to obtain a diaphragm slurry. The diaphragm coating slurry is coated on one side of a PE base film by coating, and dried at 60°C to obtain a sodium ion battery coated diaphragm.

[0045] Comparative Example 4: The difference between this comparative example and Example 1 is that only the same base film as that in Example 1 is provided, and the surface of the base film is not coated.

[0046] Test example: The coated diaphragm or base film provided in Examples 1-4 and Comparative Examples 1-4 is used to prepare a sodium ion battery, and the preparation method is as follows: Preparation of positive electrode sheet: The positive electrode active material sodium vanadium fluorophosphate, binder PVDF and conductive carbon black were mixed in a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) was added and stirred evenly to form a mixed slurry. The slurry was evenly coated on aluminum foil, placed at 120 °C for 12 h in vacuum drying, and then cut into positive electrode sheets.

[0047] Preparation of negative electrode sheets: Hard carbon, styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC) and conductive carbon black were mixed in a mass ratio of 8:0.5:0.5:1, deionized water was added and stirred evenly to form a mixed slurry, the slurry was evenly coated on aluminum foil, placed at 90 °C for 12 h in vacuum drying, and cut into negative electrode sheets.

[0048] Full battery assembly: The positive electrode sheet, the coated separator provided by the present invention, and the negative electrode sheet are sequentially stacked and assembled into an aluminum-plastic film, and the sodium hexafluorophosphate ion electrolyte is injected into the electrode to completely soak the electrode sheet, and then the soft-pack sodium ion battery is made after sealing and formation. The capacity ratio of the negative electrode to the positive electrode in the full battery is preset to 1.1, and the capacity ratio of the sodium supplement material to the positive electrode active material is preset to 0.1.

[0049] The liquid absorption rate, room temperature ionic conductivity, and thermal shrinkage of the separators of the embodiments and comparative examples, as well as the first charge specific capacity, the first discharge specific capacity, and the capacity retention rate after 50 cycles of the sodium ion full battery assembled using the separator provided by the present invention when charged and discharged at 20 mA / g at 2-4.3 V, are measured, and the results are shown in Table 1. The charge and discharge specific capacity is based on the mass of the positive electrode active material.

[0050]

[0051] It can be seen from the data in Table 1 that the liquid absorption rate of the coated diaphragm provided in Examples 1 to 4 of the present invention is not less than 220%, the ionic conductivity is not less than 0.3 mS / cm, and the thermal shrinkage rate is not more than 2%. The first discharge specific capacity of the sodium ion battery assembled with the sodium supplement diaphragm provided in Examples 1 to 4 of the present invention is not less than 90 mAh / g, and the capacity retention rate after 50 cycles at 20 mA / g is not less than 90%. The liquid absorption rate, ionic conductivity and thermal stability of the coated diaphragm or base film provided in Comparative Examples 1 to 4 are lower than those of the coated diaphragm provided in Examples 1 to 4, and the first discharge specific capacity and capacity retention rate of the sodium ion battery assembled with the diaphragm provided in Comparative Examples 1 to 4 are also lower, indicating that the battery assembled with the diaphragm provided by the present invention not only has a higher specific capacity, but also has better cycle performance, thereby highlighting the advantages of the sodium supplement diaphragm provided by the present invention.

[0052] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described or recorded in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0053] The embodiments described above are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application, and should all be included in the protection scope of the present application.

Claims

1. A sodium ion battery separator coating slurry, characterized in that: The raw materials include the following components by mass: 5 to 60 parts of sodium supplement material, 50 to 90 parts of inorganic solid electrolyte material, 0.1 to 3 parts of dispersant, 1 to 10 parts of binder, 0.1 to 5 parts of wetting agent, 0 to 2 parts of auxiliary agent and 100 to 300 parts of solvent; the sodium supplement material is a carboxyl sodium salt sodium supplement, including a combination of one or more of tetrasodium ethylenediaminetetraacetic acid, pentasodium diethylenetriaminepentaacetic acid, trisodium nitrilotriacetate, trisodium dicarboxymethylalanine, disodium iminodiacetic acid, trisodium citrate, sodium oxalate and sodium squarate.

2. The sodium ion battery separator coating slurry according to claim 1, characterized in that: The inorganic solid electrolyte material is a NASICON solid electrolyte or / and Beta-Na-Al2O3, and the particle size of the solid electrolyte powder is 0.1-50.0 μm.

3. The sodium ion battery separator coating slurry according to claim 2, characterized in that: The NASICON-type solid electrolyte is Na 3+x Zr 2-y M y Si 3-z P z O 12 (0 ≤ x ≤ 1, 0 < y ≤ 2, 0 < z ≤ 2), and the M element is one or a combination of more than one of Mg, Zn, Y, Al, Ga, In, Ge, Sn, As, Sb, Fe, Sc, Cd, Co, Ni, Cr, Mn, Ti, V, Mo, Nb, Hf, La, Lu, Ta.

4. The sodium ion battery separator coating slurry according to claim 2, characterized in that: The general formula of Beta-Na-Al2O3 is M'2O· x Al2O3(1≤ x ≤11), wherein the M' element is Na, or a mixed element of Na and one or more of Li, Mg, K, Rb, Ag, Y, Ti, and Nb.

5. The sodium ion battery separator coating slurry according to claim 1, characterized in that: The dispersant is a combination of one or more of sodium polyacrylate, polyethylene glycol, polyvinyl pyrrolidone, polymethacrylate, polyacrylic acid ammonium salt copolymer and polyvinyl alcohol; The binder is a combination of one or more of polyacrylate, polyacrylamide, polyvinyl alcohol, styrene-butadiene rubber, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polytetrafluoroethylene, carboxymethyl cellulose, sodium carboxymethyl cellulose, polymethyl methacrylate, polyacrylate and polyacrylonitrile; The wetting agent is a combination of one or more of polydimethylsiloxane, polyether-modified siloxane, polyoxyethylene ether, polyoxyethylene alkylamine, octylphenol polyoxyethylene ether, polyether siloxane, sodium dodecylbenzene sulfonate and sodium lauryl sulfate; The auxiliary agent is a combination of one or more of sodium carboxymethyl cellulose, sodium alginate, polyglycol ether, polyoxyethylene amide, polyacrylamide, titanate coupling agent and sodium perfluorooctanoate; The solvent is a combination of one or more of deionized water, N-methylpyrrolidone, N,N-dimethylformamide, N,N-diethylformamide, dimethyl sulfoxide, tetrahydrofuran, ethanol and isopropanol.

6. A sodium ion battery coated diaphragm, characterized in that: It comprises a base film; at least one side of the base film is coated with the sodium ion battery separator coating slurry as described in any one of claims 1 to 5.

7. The sodium ion battery coated diaphragm according to claim 6, characterized in that: The base film is one or a combination of polyolefin porous film, PP / PE composite film, aramid, polyimide and non-woven fabric, and has a thickness of 5 to 50 μm.

8. The sodium ion battery coated diaphragm according to claim 6, characterized in that: The sodium ion battery separator coating slurry is coated with a thickness of 0.5 to 10 μm; the coating method includes a combination of one or more of gravure roller coating, scraper coating, spin coating, spray coating, and roller coating.

9. A sodium ion battery, characterized in that: Comprising a sodium ion battery coated diaphragm as described in any one of claims 6 to 8.

Citation Information

Patent Citations

  • Preparation method of Ba ion doped Na-beta'-Al2O3 solid electrolyte and solid electrolyte prepared by using same

    CN101941835A

  • A ceramic separator of a sodium ion battery, a sodium ion secondary battery and an application thereof

    CN109244314A

  • Application of sodium supplement additive in preparation of sodium ion battery positive electrode material, sodium ion battery positive electrode material and preparation method and application of sodium ion battery positive electrode material

    CN116169290A

  • Sodium-supplementing diaphragm, preparation method thereof and sodium ion battery

    CN118073777A

  • Pre-sodium-modified composite diaphragm as well as preparation method and application thereof

    CN118173974A

Cited By

  • Negative-electrode-free sodium metal battery electrolyte as well as preparation method and application thereof

    CN119852566A

  • Sodium-supplementing diaphragm as well as preparation method and application thereof

    CN120453632A